Determinants of interest rates: Decomposing the determinants of interest rates under inflation targeting - (:unkn) unknown (Peter Lang AG, 2019)
This chapter investigates the monetary policy rule of the Central Bank of the Republic of Turkey under a structural VAR (vector autoregression) model, structurally decomposes the variations of the determinants of the monetary policy, and compares the findings with a set of inflation-targeting emerging market economies. Structural VAR methodology is used for time series analysis for Turkey whereas GMM (generalized method of moments) based panel VAR is employed for the panel of eight emerging countries. Empirical findings suggest the dominance of inflation rate in the long-term model whereas inflation rate loses its priority in the short-term model for Turkey. A group of emerging countries are observed to keep inflation as priority in the short-term model contrary to the findings for Turkey. © Peter Lang AG 2019.
Keywords: Emerging market economies; Inflation targeting; Structural VAR; Variance decomposition